Tajdid Al-Nikah as a Jember Community Tradition in Resolving Family Problems - Jk Habibi; Adji Pratama Putra; Sukron (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The tradition of Tajdid al-Nikah is currently often carried out by Javanese people, especially the Jember area, because according to the beliefs of the Jember people, by doing Tajdid al-Nikah it will make a family that was initially less than harmonious become harmonious, which initially often caused problems in the family by doing Tajdid al-nikah, according to their belief, these problems will gradually decrease. The aim is to reveal the facts that occur and phenomena in the field in accordance with Islamic law. This research uses a qualitative approach with a phenomenological design, categorized as developmental research. Data collection in this research used three techniques, namely interviews, observation, documentation. The results of this research can be concluded that the Tajdid al-Nikah tradition is for clear purposes and also for family harmony. The beliefs and convictions they believe in as well as input from community leaders or religious leaders are reasons for couples to maintain a harmonious domestic relationship after the many problems they have gone through even though there were problems in the past.